The Effect of Household Conflict on Mental Health in Children (Case Study in Sako District, Palembang) - Hammam, Hammam; Ashari, Winning Son (Al Mashaadir : Jurnal Ilmu Syariah, 2024)
Conflict is a problem, a dispute that occurs between one individual and another. Conflict itself occurs in many issues, such as households, families, children and parents, siblings and so on. Domestic life inevitably requires a change in lifestyle, adjusting to the demands of responsibility, understanding the characteristics of new people around them, and establishing good relationships between spouses. The main causes of domestic conflict include: (1) Ineffective Communication, (2) Different Values and Views, (3) Financial Issues, (4) Roles and Responsibilities, (5) Interpersonal Issues, (6) Family Crisis, (7) Life Stress. Children affected by their parents' domestic conflict can experience a range of serious mental health problems. Household conflict can make them feel isolated and lack emotional support, which can worsen their depression. Based on interviews that have been conducted most of those affected or affected by domestic conflict in their parents will become more aggressive, prone to tantrums, or withdraw from their social environment. The purpose of this study is to determine how parental conflict affects children's mental health. As well as the impact that occurs on mental health in children due to parental household conflict.  This research was conducted using the interview method with informants who have been determined. In this study, researchers used a qualitative approach to analyze the data. In addition, other data collection techniques used in this study are observation, and documentation. The conclusion in this study is that children who are raised in families that experience a lot of conflict tend to have lower social skills, emotional development, and adaptability than children their age. The result can develop into anxiety disorders, low self-esteem, inability to interact, and denial.